Efficacy of differentiated targeted interferon and immunomodulatory therapy focused on pathological immunophenotypes in patients with atypical chronic active herpesvirus infections - I. V. Nesterova; E. O. Khalturina (Медицинский вестник Юга России, 2024)
Objective: In a prospective cohort study to evaluate the clinical and immunological efficacy of differentiated targeted interferon and immunomodulatory therapies focused on identified pathological immunophenotropes and associated clinical manifestations in immunocompromised patients suffering from atypical chronic active herpes viral infections (ACA-HVI).Materials and methods: 335 patients suffering from mixed-AHA-HVI were examined. The study complex included: methods for detecting herpesviruses: serodiagnosis, PCR-RV; immunological methods: a research of subpopulation of blood lymphocytes (method of a flow cytometry), determination of the spontaneous and induced products of IFNα and IFNγ, levels of serum cytokines and immunoglobulins (IL-1β, IL-6, IL-17, TNFα and IFNα and IFNγ, Ig A, M, G) by ELISA. The study was approved by the ethics board and informed consent was obtained from all patients.Results: Integral formulas of disorders in the antiviral immune defense system were created, which made it possible to isolate 3 pathological immunophenotypes (PIF): PIF1: NG↓+ind.IFNα/IFNγ↓+CTL↓+EKK↓+IgM↑+hypecytokinemiya (IL-1β↑+IL-6↑+TNFα↑); PIF2: NG↓+ ind. IFNα/IFNγ↓ + EKK↓+ IgG↓+hypercytokinemiya (IL-1β↑+IL-6↑+TNFα↑) and PIF3: NG↓+ind.IFNα/IFNγ↓+hypercytokinemiya (IL-1β↑+IL- 6↑+TNFα↑). Taking into account the identified disorders, a program of targeted interferon and immunomodulatory therapy was developed for each PIF: local and systemic IFN therapy + hexapeptide was developed for PIF1; for PIF2- local and systemic IFN therapy + glucosaminimuramyldipeptide; for PIF3-local and systemic IFN therapy.Conclusions: High clinical efficacy was demonstrated in 100% of patients with three groups of ACA-HVI. Immunological effectiveness of targeted interferon and immunomodulatory therapy programs: 89.5% for PIF1; for PIF2-57.6% and for PIF3- 37.5% of cases.